Determinants of profitability in Mexican commercial banks. A two-stage analysis using parametric deterministic and stochastic approaches to estimate efficiency. - Mariscal Martinez, Jesus Angel (2015)
The main purpose of the dissertation is to identify the determinants of profitability of Mexican commercial banks in the period from 2010 to 2014. The observed years analyse the post-global financial crisis period where in a wide sense, a recovery of the economic and financial conditions are observed. Bank-specific and macroeconomic variables were tested, using ROE to measure the level of profitability. A two stage methodology was followed. First, the efficiency variables were estimated based on cost efficiency frontier models, where the parametric deterministic approaches COLS and MOLS, and the parametric stochastic SFA were used. For the second step, dynamic panel data regressions were used to deal with cross-sectional data of banks and years, where System GMM was used to deal with potential endogeneity. Average cost efficiency scores of 72%, 89% and 77% were estimated using the COLS, MOLS and SFA approaches, respectively. Furthermore, the results from the dynamic System GMM models confirm the dynamic nature of the Mexican commercial banking system, and indicate a moderate level of competition where larger banks tend to be the most profitable. Cost efficiency was also found as one of the main determinants of bank profitability. A noteworthy result is that national owned banks seem to be more profitable than foreign owned. The results also give evidence that if a controlled environment is assumed through the use of deterministic approaches to estimate efficiency, then the profitability relies on internal operation variables related to revenue diversification and liquidity. In the other hand, if an environment with random shocks affecting the position of the banks is assumed through the use of the stochastic approach to estimate efficiency, industry decision makers should be more aware of the macroeconomic indicators rather than in internal operations.